Ultrathin Fe‐N‐C Nanosheets Coordinated Fe‐Doped CoNi Alloy Nanoparticles for Electrochemical Water Splitting. (12th September 2018) - Zhang, Qingran; Webster, Richard F.; Cheong, Soshan; Tilley, Richard D.; Lu, Xunyu; Amal, Rose
Abstract: The development of highly active and cost‐effective catalyst materials toward electrochemical water splitting is of great importance for converting and storing the intermittent solar energy in the form of hydrogen. Herein, for the first time, an ultrathin Fe and N‐co‐doped carbon nanosheet encapsulated Fe‐doped CoNi alloy nanoparticle (FeCoNi@FeNC) composite is obtained and applied as a bifunctional catalyst for hydrogen evolution reaction (HER) and oxygen evolution reaction (OER). This catalyst exhibits prominent catalytic performances for both HER and OER, which only requires overpotentials of 102 and 330 mV, respectively, to reach a current density of 10 mA cm −2 in alkaline media. The high catalytic activity is intrinsically associated with the presence of Fe in both nanosheets and nanoparticles, which has triggered the occurrence of coordinative effects between Fe‐N‐C and FeCoNi that are beneficial for HER and OER, as revealed by electrochemical techniques. In an overall water splitting electrolyzer, FeCoNi@FeNC is employed as both the cathode and anode catalysts, achieving 12 mA cm −2 at 1.63 V for a duration of more than 12 h. Abstract : Fe and N co‐doped carbon nanosheet encapsulated Fe‐doped CoNi nanoparticles are successfully synthesized and served as efficient precious‐metal‐free bifunctional electrocatalysts for hydrogen evolution reaction and oxygen evolution reaction in alkaline with excellent catalytic performances. The two‐electrode electrolyzer using FeCoNi@FeNC composite as both cathode and anode catalysts exhibits a current density of 12 mA cm −2 at a potential of 1.63 V.